FAKTOR-FAKTOR YANG MEMPENGARUHI STATUS GIZI BALITA DI UPT PUSKESMAS ULAWENG - Hasliana Haslan (LPPM Institut Sains dan Kesehatan Bone, 2021)
Abstract. The type of research used in this study was a cross sectional study design. The number of samples that met the criteria was 30 people.Results: The results showed that a) there was an influence between knowledge and nutritional status of children under five at the UPT Puskesmas Ulaweng and the results of the chi square test showed that p-value = 0,000 p <0.05, b) There was an influence between maternal behavior and nutritional status of children under five at UPT. Puskesmas Ulaweng with the chi square test results obtained p-value = 0.004 p <0.05, c) There is an influence between maternal work and the nutritional status of children at the UPT Puskesmas Ulaweng with the chi square test results obtained p-value = 0.000 p <0.05